Pengelolaan Sampah Melalui PLTSa Di Indonesia Untuk Mewujudkan Net Zero Emission - Gresia Putri Damayanti; Waluyo Waluyo; Rosita Candrakirana (Amal Insani Foundation, 2023)
The goal of this paper is to conduct a normative analysis of the PLTSa development in Indonesia as a form of net-zero emissions policy. This research is normative and conducted through library research utilizing the statute approach method. It is done by looking normatively at the relevant statutory regulations. So, utilizing the theory developed by Hans Kelsen and Nawiasky, known as the stufenbau theory, he concentrates on the discussion of statutory regulations connected to PLTSa development in the discussion part and the study findings. Examining if different legal frameworks governing PLTSa development in Indonesia are harmonized is the goal. Additionally, the discussion and research findings in this paper draw on studies of the literature from a range of sources that address the integration of the Sustainable Development Goals (SDGs) and the principles of Good Environmental Governance in Indonesia's PLTSa development plans. According to the research in this paper, it can be concluded that PLTSa development in Indonesia can positively influence efforts to achieve net zero emissions, and that PLTSa use in waste management is a form of environmental protection that is consistent with the objectives of sustainable development. In order to develop and administer PLTSa in Indonesia, the government still needs to take into account a number of factors, starting with the implementation of these policies and statutory regulations. in order for the PLTSa policy optimization to work effectively.